The Flotation Behavior of Digested Asphalt Ridge Tar Sands (8ee488b9-1910-40de-997a-19da4f1129fe) - R. J. Smith; J. D. Miller (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
The hot water process for Utah tar sands differs significantly from that used for Canadian tar sands due to inherent differences in respective bitumen viscosities and the nature of bitumen-sand association. These differences have led to the identification of certain design criteria necessary to achieve satisfactory phase disengagement during digestion (Sepulveda and Miller, 1978; Misra and Miller, 1980). Subsequent flotation of digested tar sand is a subject of current attention and is considered in this publication for the Asphalt Ridge deposit. Although contact angle measurements of solvent extracted Asphalt Ridge bitumen indicated moderate hydrophobicity, air bubble attachment to the bitumen concentrate is not possible. This surprising result suggests that flotation separation is dependent on air bubble entrapment rather than on air bubble attachment due to surface hydrophobicity. The entrapment of air bubbles in the bitumen was apparent from examination of the bitumen concentrate, especially at lower flotation temperatures. A factorial design of the major operating variables in flotation separation indicated that the quality of separation was significantly dependent on the flotation temperature and to a lesser extent on the degree of agitation. For a flotation temperature of 77°C a recovery of 96.7% was realized at a grade of 61.0% bitumen. The improved separation at higher flotation temperatures was found to be due to the decrease in bitumen viscosity resulting in more effective rejection of coarse sand from the concentrate. This research effort, which has been sustained for the past six years at the University of Utah, is being continued to provide necessary design data for the construction of a pilot plant to treat Utah tar sands.